An Excel VBA‐based educational module for bed roughness predictors. Issue 5 (26th October 2020) - Niazkar, Majid
Abstract: Estimation of flow resistance coefficients plays an inevitable role in open‐channel flows in hydraulic modeling and water resources engineering. Despite many equations and methods recommended for estimating roughness coefficients, only two standard resistance equations (original Manning's and Keulegan's equations) have been widely taught and utilized in practice. There can be various reasons for not using new bed roughness predictors (BRPs),  one of which is the absence of teaching BRPs. A rigorous analysis of available BRPs for estimating grain and form roughness coefficients delineates that most of them are comprised of a scheme rather than a single equation. Also, each BRP is tailored to solve a distinct type of problem; however, a proper definition of a problem statement helps shedding light on this application. This study presents an Excel VBA‐based educational estimator to address the gap. For this purpose, the problem statement is first revisited to accomplish a better understanding in light of proper problem classification. On the basis of different groups of input and output data, each BRP is implemented into an Excel spreadsheet and VBA codes are presented for BRPs incorporating both grain and form roughness. This computer application can help students in open‐channel engineering courses not only to become familiar with modified BRPs but also to acknowledge the merit of the Excel spreadsheet for estimating flow resistance coefficients. Finally, as the VBA codes are presented in detail, they can be modified by users in accordance with their priorities for both educational and practical purposes.